2015
DOI: 10.1073/pnas.1507307112
|View full text |Cite|
|
Sign up to set email alerts
|

Competition and allostery govern substrate selectivity of cyclooxygenase-2

Abstract: Cyclooxygenase-2 (COX-2) oxygenates arachidonic acid (AA) and its ester analog, 2-arachidonoylglycerol (2-AG), to prostaglandins (PGs) and prostaglandin glyceryl esters (PG-Gs), respectively. Although the efficiency of oxygenation of these substrates by COX-2 in vitro is similar, cellular biosynthesis of PGs far exceeds that of PG-Gs. Evidence that the COX enzymes are functional heterodimers suggests that competitive interaction of AA and 2-AG at the allosteric site of COX-2 might result in differential regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
54
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 37 publications
4
54
0
Order By: Relevance
“…However, the compounds are not able to establish the same HB interactions with residues Arg120 and Tyr355. [21] Compound 3, 13, and 14 block the entrance to the main pocket of COX-2 in different extents. Compounds 6 and 7 are located outside the pocket, establishing some π-stacking interactions with aromatic side chains of residues Tyr115 and Tyr355.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…However, the compounds are not able to establish the same HB interactions with residues Arg120 and Tyr355. [21] Compound 3, 13, and 14 block the entrance to the main pocket of COX-2 in different extents. Compounds 6 and 7 are located outside the pocket, establishing some π-stacking interactions with aromatic side chains of residues Tyr115 and Tyr355.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…Recent studies revealed that only one monomer of the COX homodimer is active at a given time [29]. It has been postulated that these monomers can act additionally through an allosteric/catalytic couple, with AA oxygenation being controlled in the 'catalytic' monomer (E cat ) through the binding of non-substrate faty acids and nonselective NSAIDs to the opposite monomer, the 'allosteric' monomer (E allo ) [30,31]. Moreover, the major diferences between COX-1 and COX-2 are the substitutions of the bulkier amino acid residues Ile434, His513 and Ile523 in COX-1 by comparatively smaller residues Val434, Arg513 and Val523, respectively, in COX-2 at the main channel of cyclooxygenase binding site (Figure 3).…”
Section: Structural and Functional Insights Of Cyclooxygenase Enzymesmentioning
confidence: 99%
“…One subunit in the dimer harbors the catalytically active site, while the other subunit contains an allosteric site that modulates the overall activity of the enzyme (Dong et al, 2013, 2011; Kulmacz and Lands, 1984). An array of substrates, inhibitors, and allosteric modulators can bind to, and thus compete for, either site, giving rise to highly complex reaction kinetics (Kudalkar et al, 2015; Kulmacz and Lands, 1985; Mitchener et al, 2015; Rimon et al, 2010; Yuan et al, 2009; Dong et al, 2016a). The various products from COX-2 activity drive multiple downstream pro- and anti-inflammatory processes that lead to diverse cellular fates including stress responses and apoptosis (Funk, 2001; Rouzer and Marnett, 2003; Smith et al, 2000).…”
mentioning
confidence: 99%
“…Previously, most studies of COX-2 function have used simplified models based on Michaelis-Menten kinetics (Briggs and Haldane, 1925). Not surprisingly, these approaches have proved insufficient to capture the rich complexity of the COX-2 network of reactants, intermediates and products (Mitchener et al, 2015). We posit that a systems approach to understand COX-2 mechanism will improve inhibitor design to achieve desired outcomes in clinical settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation